Before and beyond EMU : historical lessons and future prospects - Crowley, Patrick M. (London ; New York : Routledge, 2002)
The focus of the collection of papers is on the background to EMU and future prospects of the EU.
Includes bibliographical references and index.
osc 2/9/16
Loans
Keywords: Monetary unions; Monetary policy; Europe